2022
DOI: 10.1002/ejsp.2859
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond simplicity: Using machine learning to predict belief in conspiracy theories

Abstract: Public and scientific interest in why people believe in conspiracy theories (CT) surged in the past years. To come up with a theoretical explanation, researchers investigated relationships of CT belief with psychological factors such as political attitudes, emotions, or personality. However, recent studies have put the robustness of these relationships into question. In the present study, a prediction-based analysis approach and machine learning models are deployed to detect and remedy poor replicability of CT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 131 publications
(194 reference statements)
2
2
0
Order By: Relevance
“…The first four of these predictors were more powerful than any country‐level predictors. For the most part, these individual‐level predictors are in line with prior theory and research, including the results of a similar machine‐learning analysis by Brandenstein (2022). Research has found that conspiracy theorizing is be associated with a negative view of elites, disillusionment with society, paranoia and frustrated psychological needs (Douglas et al., 2017, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The first four of these predictors were more powerful than any country‐level predictors. For the most part, these individual‐level predictors are in line with prior theory and research, including the results of a similar machine‐learning analysis by Brandenstein (2022). Research has found that conspiracy theorizing is be associated with a negative view of elites, disillusionment with society, paranoia and frustrated psychological needs (Douglas et al., 2017, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…The first four of these predictors were more powerful than any country-level predictors. For the most part, these individual-level predictors are in line with prior theory and research, including the results of a similar machine-learning analysis by Brandenstein (2022).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations